Perceptions of Commercial Integrated Library Management System (ILMS) Users on Open Source Packages with a Special Reference to Libsys Software - Gireesh Kumar, T. K. (Journal of Information and Knowledge, 2016)
Advent of Information and Communication Technology has highly influenced the entire spectrum of libraries worldwide. As an effective solution to automate the activities and services of libraries, Integrated Library Management System is increasingly gaining momentum in Indian libraries for the last few decades. Among them, popularity of Open Source Integrated Library Management System (OSILMS) is increasing as a cost effective solution to automate the library due to its provisions in self-customizing to meet the local requirements. However, it is true that majority of the Indian libraries are still continuing with their legacy commercial systems, though they have awareness of advantages of OSILMS. In this context, this research study observes the major issues associated with the adoption of OSILMS in Indian libraries and examines the attitude of library professionals using LibSys software towards the adoption of OSILMS. The present paper also investigates the major concerns why LibSys software is being used as a commercial automation system when OSILMS are available for free and the study also analyzes the satisfaction level of LibSys users with the functional modules of the software. Majority of LibSys users support the adoption of OSILMS though they are satisfied with their software being used, however lack of technical knowledge, support and shortage of skilled staff required to install and maintain the software are found to be the major issues associated with the adoption of OSILMS in Indian libraries.